2012
DOI: 10.1254/jphs.11236fp
|View full text |Cite
|
Sign up to set email alerts
|

Anandamide Induces Endothelium-Dependent Vasoconstriction and CGRPergic Nerve–Mediated Vasodilatation in the Rat Mesenteric Vascular Bed

Abstract: An endogenous cannabinoid anandamide (N-arachidonoylethanolamide) has been shown to cause vasodilatation in vitro and a brief vasoconstriction followed by prolonged depressor response in vivo. This study investigated the vascular effects of anandamide and underlying mechanisms in rat mesenteric vascular beds. In preparations with an intact endothelium and active tone, anandamide at low concentrations (0.1 - 1 nM) caused a concentration-dependent decrease in perfusion pressure due to vasodilatation, but at high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 43 publications
1
8
0
2
Order By: Relevance
“…Moreover, the activation of TRPV1 channels may induce vasodilation via increased release of calcitonin gene-related peptide (CGRP). 33 In support of this, recent findings indicate that the activation of TRPV1 channels through capsaicin ingestion modulate vascular function by opposing a-adrenergic receptor-mediated vasoconstriction and potentiating vasorelaxation. 34 Hence, the observed lower total peripheral resistance is possibly linked with the capsaicin-induced vasorelaxation or with NO increase and/or CGRP release.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Moreover, the activation of TRPV1 channels may induce vasodilation via increased release of calcitonin gene-related peptide (CGRP). 33 In support of this, recent findings indicate that the activation of TRPV1 channels through capsaicin ingestion modulate vascular function by opposing a-adrenergic receptor-mediated vasoconstriction and potentiating vasorelaxation. 34 Hence, the observed lower total peripheral resistance is possibly linked with the capsaicin-induced vasorelaxation or with NO increase and/or CGRP release.…”
Section: Discussionmentioning
confidence: 86%
“…Noteworthily, Yang et al observed that TRPV1 activation by capsaicin enhanced endothelium‐dependent vasorelaxation and that this effect was absent in TRPV1 deficient mice. Moreover, the activation of TRPV1 channels may induce vasodilation via increased release of calcitonin gene‐related peptide (CGRP) . In support of this, recent findings indicate that the activation of TRPV1 channels through capsaicin ingestion modulate vascular function by opposing a‐adrenergic receptor‐mediated vasoconstriction and potentiating vasorelaxation .…”
Section: Discussionmentioning
confidence: 95%
“…CB 1 receptors are not involved in the AEA-mediated vasorelaxation since the respective receptor antagonist AM251 (1 μM; Wheal et al 2010) did not influence the CRC of anandamide. The involvement of CB 2 and vanilloid TRPV1 receptors could also be excluded since the respective antagonists at these receptors, SR144528 (1 μM; Kozłowska et al 2008) and capsazepine (1 μM; Tamaki et al 2012), failed to modify the vasorelaxant effect of anandamide. By contrast, O-1918 (10 μM; pA 2  = 6.3 and 6.0; Kozłowska et al 2008; Baranowska-Kuczko et al 2012, respectively) shifted to the right of the CRC for anandamide, suggesting that this receptor plays a role in the anandamide-induced vasorelaxation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, dietary capsaicin enhances TRPV1 expression in endothelial cells, and this response is associated with an increase in endothelium-dependent vasodilation ( 68 ). The activation of the TRPV1 channels also induces vasodilation via increased release of the calcitonin gene-related peptide at the nerve terminals of capsaicin-sensitive neurons that innervate peripheral arteries ( 70 ). This vasodilation seems to mediate the decrease in blood pressure observed after the administration of TRPV1 agonists.…”
Section: Cardiovascular Systemmentioning
confidence: 99%